2018
DOI: 10.1177/0269215517752488
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into the patient-centered goal-setting practices of allied health clinicians working in rehabilitation

Abstract: Goals developed with rehabilitation patients are more likely to be patient-centered when the interaction encourages the patient to express their needs and preferences, and these are heard by the clinician. For this to influence treatment, it must occur in an environment structured to support and value patient-centered goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…This also resonates with other published evidence describing a continuum of goal setting approaches, from 'patient-led' at one end to 'health professional' led at the other, along which person-centered goal setting was possible. 23,45,46 Cameron et al, 46 in their ethnographic study, highlighted active and reflective listening by practitioners as being crucial to achieving the level of collaboration required for successful patient-centred goal setting, recognizing that most patients have the ability to direct goal setting conversations when supported.…”
Section: Person-centered Goal Setting Is Possible But Often Does Not mentioning
confidence: 99%
See 2 more Smart Citations
“…This also resonates with other published evidence describing a continuum of goal setting approaches, from 'patient-led' at one end to 'health professional' led at the other, along which person-centered goal setting was possible. 23,45,46 Cameron et al, 46 in their ethnographic study, highlighted active and reflective listening by practitioners as being crucial to achieving the level of collaboration required for successful patient-centred goal setting, recognizing that most patients have the ability to direct goal setting conversations when supported.…”
Section: Person-centered Goal Setting Is Possible But Often Does Not mentioning
confidence: 99%
“…A positive and engaging therapeutic relationship seemed to foster more of the same, whereas a relationship where practitioner and stroke survivor goals were not aligned led to discontentment, resignation and sometimes to the stroke survivors keeping their own goals secret. Cameron et al 46 found practitioners had greater influence on the goals developed than patients, highlighting practitioner self-awareness as a key factor in the success of goal setting. However, they also reported a perceptual-practice gap where practitioners may overestimate the extent to which their goal setting was person-centred.…”
Section: Practitioners Shape the Context Of Goal Setting (Level 2 Heamentioning
confidence: 99%
See 1 more Smart Citation
“…The client-centred approach is highlighted in occupational therapy models (6,7) and recommended for rehabilitation after stroke in order to achieve a successful rehabilitation outcome. To increase the clients' involvement in the rehabilitation process it is important to collaborate with the client, and to focus on the needs and wishes of the client (8)(9)(10). Being able to participate in meaningful activities can promote health and life satisfaction for people with long-term conditions such as stroke, and is often expressed as the overall goal in rehabilitation (11,12).…”
mentioning
confidence: 99%
“…28. Lisa J Cameron et al, 2018 et al ., “A qualitative investigation into the patient-centred goal-setting practices of allied health clinicians working in rehabilitation,” Clin Rehabil 32, no. 6 (Jun 2018),…”
mentioning
confidence: 99%